Electric motor drives modeling, analysis and control - Krishnan, Ramu (Prentice Hall, 2001)
Designed for introductory (senior) level and graduate level courses in electric drives/power electronics, this book develops a systematic approach to motor drives. While the emphasis is on practice; extensive modeling, simulation and analysis is developed to assist readers in their understanding of the subject matter from fundamental principles.